Ice shelf fracture parameterization in an ice sheet model - Stephen Cornford (The Cryosphere, 2017)
We add a continuum damage model to the BISICLES AMR ice sheet model to simulate crevasse growth and transport, and test its impact on a standard test. We conclude that damage mechanics are important in ice shelves, and reduce their drag upon upstream glaciers, but that models may perform similarly with simple rules-of-thumb.